An expert system based headache solution - Hasan, Md. Rajib; Sumon, Md. Shariful Hasan; Siraj, Fadzilah (IEEE, 2012)
Human is becoming busier, and the rush hours can cause physical and mental stresses. In many countries, it is found that the patients in neurological department are increasing randomly. However, the numbers of doctors are not sufficient to serve the patients. Furthermore, at times the doctors need other doctors’ opinion in supporting the decision making. This paper investigates the potential developing of an expert system for headache detection.